Going beyond the disability-based morbidity definition in the compression of morbidity framework - Hiram Beltrán-Sánchez; Fahad Razak; S. V. Subramanian (Taylor & Francis Group, 2014)
Background: As originally proposed by Fries, conceptualizing morbidity solely through associated functional limitation/disability (FL/D) remains the most widely accepted metric to assess whether increases in longevity have been accompanied by a compression of morbidity. Objective: To propose a departure from a highly restrictive FL/D-based definition of "morbidity" to a broader view that considers the burden of chronic diseases even when no overt FL/D occur. Design: We outline three reasons why the current framework of compression of morbidity should be broadened to also consider morbidity to be present even when there are no overtly measurable FL/D. We discuss various scenarios of morbidity compression and morbidity expansion under this broader rubric of morbidity. Conclusion: The rationale to go beyond a purely FL/D-based definition of morbidity includes: (1) substantial damage from chronic disease that can develop prior to overt FL/D symptoms occurring; (2) multiple costs to the individual and society that extend beyond FL/D, including medication costs, health care visits, and opportunity costs of lifelong treatment; and (3) psychosocial and stress burden of being labeled as diseased and the consequence for overall well-being. Adopting this broader definition of morbidity suggests that increases in longevity have been possibly accompanied by an expansion of morbidity, in contrast to Fries' original hypothesis that morbidity onset (based on only FL/D) would be delayed to a greater extent than increases in survival. There is an urgent need for better data and more research to document morbidity onset and its link with increases in longevity and assess the important question on whether populations while living longer are also healthier.